Seasonal and Landscape‐Driven Variations in Forage Resources of Apis mellifera scutellata: Implications for Pollination Sustainability and Colony Health in Taita Taveta County, Kenya - Mary Chege; Mbatha B. Wambua; Wambua J. Kilonzo; Sevgan Subramanian; Beatrice T. Nganso (Ecology and Evolution, 2025)
ABSTRACT Seasonality and land‐use change are key factors influencing forage availability for managed honey bee colonies, yet knowledge of forage identity and how these factors influence forage availability remains limited in Africa. To address these gaps, we used DNA metabarcoding to identify nectar and pollen plant species supporting the nutrition of the African savannah honey bee, Apis mellifera scutellata, across different land‐use/land cover types and seasons in Taita Taveta County, Kenya. We identified 224 forage plant species from 65 families, with Asteraceae, Fabaceae, and Myrtaceae being the top contributors. Forage availability was significantly influenced by landscape and season, with honey bees in agricultural lowland areas foraging on fewer and less diverse resources, particularly pollen, than those in forested highland and midland areas during the short dry season. Nectar plants (the primary source of carbohydrates that support energetic needs) were generally more diverse than pollen plants (the main source of proteins and lipids that support development and health). Exotic species dominated the nutrition of A. m. scutellata (67%) compared to native species (33%), raising concerns about the long‐term sustainability of local pollination networks, pollinator health, and productivity. Overall, these findings provide a foundation for future research on the comparative nutritional composition of both native and exotic plants across seasons, their impacts on honey bee health and productivity, and how the occurrence of exotic plants may affect local plant‐pollinator networks, to guide the development of nutrient‐rich forage landscapes for honey bees in this county.